PENGEMBANGAN LKPD MATEMATIKA BERBASIS ETNOMATEMATIKA PERMAINAN TRADISIONAL CONGKLAK UNTUK KELAS II SD - Nabila, Nabila; Sastrawati, Eka; Budiono, Hendra (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This study aims to develop mathematics worksheets (LKPD) using traditional game-based ethnomathematics of congklak for second-grade elementary school students and evaluate their feasibility. Research and Development (RD) methodology, employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), was utilized. Data collected included qualitative and quantitative data from SDN 182/I Hutan Lindung during January-February 2024 through validation questionnaires completed by experts and interviews with teachers and students. The data were analyzed to assess the feasibility of the developed ethnomathematics-based LKPD. The outcome is a highly valid and practical mathematics worksheet for second-grade elementary school students, as indicated by average scores of 5 from subject matter, media, and language experts, and teacher response questionnaires. Student response questionnaires in small group trials averaged 4.33, while in large group trials, they averaged 4.58, both showing high practicality. Thus, it can be concluded that the developed mathematics worksheets based on traditional game-based ethnomathematics of congklak are highly valid and practical for second-grade elementary school students.